2017
DOI: 10.1186/s13071-017-2195-4
|View full text |Cite
|
Sign up to set email alerts
|

Description of Culicoides (Culicoides) bysta n. sp., a new member of the Pulicaris group (Diptera: Ceratopogonidae) from Slovakia

Abstract: BackgroundSpecies of the genus Culicoides Latreille, 1809 (Diptera: Ceratopogonidae) are mainly known as vectors of arboviruses such as bluetongue (BTV) and Schmallenberg (SBV). Among the known vectors, few species within the subgenus Culicoides Latreille, 1809 have been implicated in the transmission of BTV and SBV. Nevertheless, phylogenetic studies had revealed the presence of cryptic and undescribed species in Europe, raising questions about their vectorial role. A previous integrative study, associating m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…nov. [27]. In a Turkish study, three different haplotypes of C. lupicaris were recovered [27][28][29][30] and results obtained here indicate a similar situation in C. pulicaris.…”
Section: Information On Seasonal and Spatial Distribution Patterns As Well As Autecology Of Differentsupporting
confidence: 77%
“…nov. [27]. In a Turkish study, three different haplotypes of C. lupicaris were recovered [27][28][29][30] and results obtained here indicate a similar situation in C. pulicaris.…”
Section: Information On Seasonal and Spatial Distribution Patterns As Well As Autecology Of Differentsupporting
confidence: 77%
“…DNA barcoding is an important tool in biodiversity studies [53][54][55][56][57]. Thereby, barcoding also helped to identify cryptic and new Culicoides species [58][59][60]. In this study, successful sequencing of 1040 engorged insects demonstrated that barcoding is a useful tool for both, Culicoides and host identification.…”
Section: Discussionmentioning
confidence: 71%
“…One difficulty as presented by some studies where CO1 sequencing and, perhaps, that of another gene or two is used as a phylogenetic tool is that they often concern relatively small groups of morphologically similar species such as species groups of Culicoides (Ander et al, 2013;Bakhoum et al, 2013;Bellis et al, 2014;Harrup et al, 2016;Muñoz-Muñoz et al, 2014;Pagès et al, 2009;Sarvašová, et al, 2017;Talavera et al, 2017;Tay et al, 2016). Morphologically-based synapomorphies are less likely to be evident (or present) in such similar species groups.…”
Section: Genomes Vs Phenotypementioning
confidence: 99%